The Long‐Term Effectiveness of a Multisetting Lifestyle Intervention on Tobacco‐Related Habits in Adolescent Boys and Girls: Tehran Lipid and Glucose Study. (18th May 2022) - Masihay‐Akbar, Hasti; Amiri, Parisa; Rezaei, Marjan; Jalali‐Farahani, Sara; Cheraghi, Leila; Momenan, Amir Abbas; Azizi, Fereidoun
ABSTRACT: BACKGROUND: This study assesses the long‐term effectiveness of a lifestyle intervention on cigarette, passive, and hookah smoking in adolescent boys and girls. METHODS: One thousand one hundred and fifty‐nine adolescent participants of Tehran Lipid and Glucose Study (TLGS) (2001‐2004) were followed for 12 years. Participants in the intervention area received lifestyle interventions in family, schools, and community settings, with the largest part implemented in schools. After excluding those with missing baseline parental data (n = 66), complete parental data of 1093 adolescents was used for cluster analysis. Families were classified as low‐ and high‐risk. Two hundred and ninety‐six individuals who did not complete intervention/follow‐ups were excluded, GEE was performed on 797 adolescents (369 boys, 192 intervention) to assess the intervention effect on tobacco‐related habits. RESULTS: Adolescents' mean baseline age was 15.21 ± 1.95. Those living in high‐risk families were more at risk of cigarette, passive, and hookah smoking. Intervention decreased odds of cigarette and passive smoking by 38% and 57%, respectively. Intervention did not reduce hookah smoking in adolescents. After sex‐specific analysis, the intervention reduced current cigarette smoking by 40% only in boys and passive smoking in both sexes. CONCLUSIONS: Targeting lifestyle behaviors in school‐aged adolescents and their families reduces cigarette smoking in boys and protects both sexes from secondhand smoke.